Performance study of imitated syngas in a dual-fuel compression ignition diesel engine - Mahgoub, B.K.M. (Universiti Malaysia Pahang, 2015)
Operating engines fueled by syngas and diesel is an available renewable option to avert concerns related to the supply of petroleum and the environment. But the use of syngas in a compression ignition (CI) diesel engine leads to a reduction in the power output because of its lower heating value compared with the 100 diesel mode. Furthermore, it is not easy to evaluate the performance of real syngas due to the varying gas content when inducted into a CI diesel engine. In this study, a single-cylinder, two-stroke, naturally aspirated CI diesel engine was operated with imitated syngas as the primary fuel in dual-fuel mode. The objective of this study is to investigate the effect of syngas composition on the performance of a dual-fuel engine running at different engine speeds (1200, 2000, 3000 rpm). The impact of engine speed on the performance of syngas in the dual-fuel CI diesel engine was examined at various diesel replacement ratios (DR). Composition C showed the best results for engine performance compared to other compositions. Â© Universiti Malaysia Pahang.